Comprehensive analysis of the association of seasonal variability with maternal and neonatal nutrition in lowland Nepal. Issue 7 (23rd July 2022) - Saville, Naomi M; Cortina-Borja, Mario; De Stavola, Bianca L; Pomeroy, Emma; Marphatia, Akanksha; Reid, Alice; Manandhar, Dharma S; Wells, Jonathan CK
Abstract: Objective: To provide a comprehensive seasonal analysis of pregnant mothers' eating behaviour and maternal/newborn nutritional status in an undernourished population from lowland rural Nepal, where weather patterns, agricultural labour, food availability and disease prevalence vary seasonally. Design: Secondary analysis of cluster-randomised Low Birth Weight South Asia Trial data, applying cosinor analysis to predict seasonal patterns. Outcomes: Maternal mid-upper arm circumference (MUAC), BMI, dietary diversity, meals per day, eating down and food aversion in pregnancy (≥31 weeks' gestation) and neonatal z-scores of length-for-age (LAZ), weight-for-age (WAZ) and head circumference-for-age (HCAZ) and weight-for-length (WLZ). Setting: Rural areas of Dhanusha and Mahottari districts in plains of Nepal. Participants: 2831 mothers aged 13–50 and 3330 neonates. Results: We found seasonal patterns in newborn anthropometry and pregnant mothers' anthropometry, meal frequency, dietary diversity, food aversion and eating down. Seasonality in intake varied by food group. Offspring anthropometry broadly tracked mothers'. Annual amplitudes in mothers' MUAC and BMI were 0·27 kg/m 2 and 0·22 cm, with peaks post-harvest and nadirs in October when food insecurity peaked. Annual LAZ, WAZ and WLZ amplitudes were 0·125, 0·159 and 0·411 z-scores, respectively. Neonates were the shortest but least thin (higher WLZ) in winter (December/January). In the hot season, WLZ was the lowest (May/June) while LAZ was the highest (March and August). HCAZ did not vary significantly. Food aversion and eating down peaked pre-monsoon (April/May). Conclusions: Our analyses revealed complex seasonal patterns in maternal nutrition and neonatal size. Seasonality should be accounted for when designing and evaluating public heath nutrition interventions.